2004
DOI: 10.1180/0026461046810177
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structures of kidwellite and ‘laubmannite’, two complex fibrous iron phosphates

Abstract: The previously unknown, complex crystal structures of two fibrous ferric iron phosphate minerals have been solved using single-crystal X-ray diffraction data. The structure of a slightly arsenatian kidwellite has been refined in space group P2/c (a = 20.117 (4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A complete characterisation of the mineral was only possible after a crystal fragment was finally found that was suitable for a single-crystal structure determination. A preliminary characterisation of the new mineral was given by Kolitsch et al (2004). The mineral and its name were unanimously approved by the Commission on New Minerals and Minerals Names, IMA (no.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete characterisation of the mineral was only possible after a crystal fragment was finally found that was suitable for a single-crystal structure determination. A preliminary characterisation of the new mineral was given by Kolitsch et al (2004). The mineral and its name were unanimously approved by the Commission on New Minerals and Minerals Names, IMA (no.…”
Section: Introductionmentioning
confidence: 99%
“…The present work is part of studies devoted to the crystal chemistry of several complex fibrous iron phosphate minerals (Kolitsch, 1999(Kolitsch, , 2001(Kolitsch, , 2004.…”
Section: Introductionmentioning
confidence: 99%